Wall Shear Rates in Taylor Vortex Flow - V. Sobolik; T. Jirout; J. Havlica; M. Kristiawan (Journal of Applied Fluid Mechanics, 2011)
Wall shear rate and its axial and azimuthal components were evaluated in stable Taylor vortices. The measurements were carried out in a broad interval of Taylor numbers (52-725) and several gap width (R1/R2 = 0.5 – 0.8) by two three-segment electrodiffusion probes and three single probes flush mounted in the wall of the outer fixed cylinder. The axial distribution of wall shear rate components was obtained by sweeping the vortices along the probes using a slow axial flow. The experimental results were verified by CFD simulations. The knowledge of local wall shear rates and its fluctuations is of primordial interest for industrial applications like tangential filtration, membrane reactors and bioreactors containing shear sensitive cells.